CAPITAL STRUCTURE DETERMINANTS: EVIDENCE FROM PALESTINE AND EGYPT STOCK EXCHANGES - Abdul Hadi, Abdul Razak; Suryanto, Tulus (Universitas Islam Negeri Raden Intan Lampung, 2016)
Abstract -This study is driven by the motivation to examine the capital structure determinants for Palestine Stock Exchange (PEX) and Egypt Stock Exchange (EGX). Within the framework of capital structure theories, this study uses Generalized Method of Moments (GMM,1982) as an estimation model employing quarterly panel data analysis during the observed period from 2008 till 2012. The test results from GMM indicate that all the examined determinants have significant relationship with leverage. It has a negative value with liquidity, non-debt tax shield, profitability, size and growth. The Egyptian firms have some uniqueness in its trend. Current assets, debt ratio and liquidity behave positively with leverage except for growth. The other tested determinants in Egyptian companies are found to be not significant.